Effect of Nitrogen and Boron in Seed Yield and Yield Attributing Characters of Broccoli - Khanal, A. (International Journal of Applied Sciences and Biotechnology, 2015)
Plant nutrient is one of the limiting factors affecting crop production. Nitrogen and boron are major nutrients in case of broccoli. So, an experiment was carried out to evaluate the effect of nitrogen and boron in seed yield and yield attributing characters of broccoli in Rampur, Chitwan during winter season. The experiment was laid out in factorial RCBD design with four levels of nitrogen and two levels of boron. Each plot consists of 25 plants which were separated by 60 * 60 cm spacing. There are altogether eight treatments replicates thrice. Local variety Calabrese was used. Significant effect of different dose of nitrogen and boron on yield attributing characters was found. Also interactive effect of nitrogen and boron in number of pods, pod length, seed yield and number of seeds per pod was found significantly different. Int J Appl Sci Biotechnol, Vol 3(3): 541-544